Electrocardiographic Manifestations of Immune Checkpoint Inhibitor Myocarditis. Issue 18 (2nd November 2021) - Power, John R.; Alexandre, Joachim; Choudhary, Arrush; Ozbay, Benay; Hayek, Salim; Asnani, Aarti; Tamura, Yuichi; Aras, Mandar; Cautela, Jennifer; Thuny, Franck; Gilstrap, Lauren; Arangalage, Dimitri; et al.
Abstract : Supplemental Digital Content is available in the text.